Influence of extraction techniques on the phytochemical contents and antioxidant properties of Pometia pinnata seed extracts - POPI PATILAYA; IMAM BAGUS SUMANTRI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Patilaya P, Sumantri IB. 2025. Influence of extraction techniques on the phytochemical contents and antioxidant properties of Pometia pinnata seed extracts. Biodiversitas 26: 3582-3589. Matoa (Pometia pinnata) seeds contain phytochemicals with vigorous antioxidant activity. However, their antioxidant activity may be affected by extraction techniques. Here, we report the impacts of extraction techniques on the chemical constituents and antioxidant properties of P. pinnata seed extracts. The plant seeds were collected in Medan (Indonesia) in January 2020. The seed extracts, obtained by maceration and Soxhlation, were evaluated for their phytochemicals and antioxidant properties. GraphPad Prism 10 was used to analyze the data, with one-way ANOVA and Tukey’s tests at a 5% significance level. The results demonstrated that the extraction yields of P. pinnata seeds obtained by maceration (10.41-38.63%) were slightly lower than those by soxhlation (15.95-49.78%). The total phenolic contents of extracts obtained by maceration (EM) and soxhlation (ES) were 25.29-46.88 mg g-1 and 46.46-93.26 mg g-1, respectively. The total flavonoid contents of EM and ES were 0.90-11.77 mg g-1 and 3.25-20.78 mg g-1, respectively. In the antioxidant assay, IC50 values of EM and ES were 63.95-1035.14 µg mL-1 and 37.25-102.02 µg mL-1, respectively. The results suggest that soxhlation was more effective than maceration, yielding higher phytochemical contents and antioxidant properties of P. pinnata seed extracts.